Simultaneous real-time multicomponent fluorescence and reflectance imaging method for fluorescence-guided surgery - Dimitriadis, Nikolas; Grychtol, Bartłomiej; Behr, Tobias; Deliolanis, Nikolaos C. (Optics letters, 2016)
Fluorescence-guided surgical procedures are employed in an increasing number of applications such as tumor delineation, blood perfusion, and sentinel lymph node detection. A new generation of fluorescent probes is expected to increase the number of applications and improve efficiency. Yet, there are no available imaging methods to take full advantage of the forthcoming targeting technologies. We present a novel concept for imaging multiple agents for fluorescence-guided surgery. The system operates without any moving parts and can resolve images of three different fluorochromes while simultaneously recording conventional reflectance images.